Enhanced thermal-operating stability of high-frequency magnetic behavior for FeMnSiBNbCu nano-structural cores via field-annealing. (June 2021) - Yang, Fuyao; Zhang, Bojun; Man, Sida; Ma, Guang; Chen, Xin; He, Aina; Liu, Yang; Dong, Yaqiang; Han, Yu
Abstract: Improving thermal-operating stabilization of soft-magnetic performances for Fe-based amorphous and nanocrystalline materials is vital for reliable and functional application. Herein, we found that the transverse magnetic-field annealed Fe74 Mn2 Si13 B8 Nb2 Cu1 nano-structural alloy with an uniaxial anisotropy has negligibly unchanged distribution and grain size of α-Fe(Si) nano-grains and magnetic domain structure during thermal-operating, thus existing an excellent thermal-stability of magnetic properties. Its permeability at 100 kHz and core loss at 0.2 T and 100 kHz in the operating temperature of 160 °C increases 2.8% and decreases 3.5% with respect to that at room temperature, respectively, which is largely different from that of the normal-annealed alloys with only effective random anisotropy. The magnetic structure characterization demonstrates local induced anisotropy energy created with thermal-operating is suppressed by the magnetic-field induced anisotropy energy, leading to the enhancement of thermal-operating stability for nano-structural alloys with high magnetic induction via magnetic-field annealing. Highlights: MFA can improve high-frequency feature and thermal-operating stability. The MFA alloy exhibits stable μ and P from room temperature to 160 °C. Distribution, size and phase structure of nano-grains are insensitive to the operating temperature. The stable softness for MFA alloy is due to the induced anisotropy dominating over local anisotropy.